Some Digenetic Trematodes of Marine Fishes from Israel's Mediterranean Coast and Their Zoogeography, Especially Those from Red Sea Immigrant Fishes - Fischthal, J. H. (Zoologica Scripta, 1980)
A total of 500 fishes (59 species) from Israel's Mediterranean coastal waters were examined for digenetic trematodes and 201 (40.2%) harbored at least one species. One new genus (Propar-vipyrum) and 11 new species are described: Bacciger israelensis (Fellodistomidae) from Sarpa salpa and Boops boops; Ancylocoelium israelense and Chrisomon israelensis (both Monor-chiidae) from Atule djeddaba; Diphtherostomum israelense (Zoogonidae) from Diplodus sargus, D. vulgaris and Saurida undosquamis; Proparvipyrum israelense (Zoogonidae) from Mullus surmuletus; Acanthocolpoides israelensis (Lepocreadiidae) from Sardinella maderen-sis; Neolepidapedon israelense (Lepocreadiidae) from Mullus surmuletus; Podocotyle jaffen-sis (Opecoelidae) from Denlex filosus; Podocotyle (Pedunculotrema) israelensis frqm Pomadasys incisus and Pelates quadrilineatus; Lecithochirium haifense (Hemiuridae) from Atule djeddaba; Lecithochirium israelense from Trachinus araneus and Scyris alexandrina. 36 previously known species were identified, and all represent new geographical distribution records. Some Red Sea immigrant fishes brought trematodes with them to the Mediterranean and some acquired Atlanto-Mediterranean species.